Characterization of oropharyngeal dysphagia screening in hospitalized adults (Research, Society and Development, 2026)
Introduction: In the hospital setting, dysphagia is a frequent symptom among patients requiring speech-language pathology (SLP) intervention. It can compromise the safe ingestion of food, liquids, and saliva, adversely affect quality of life, and lead to complications such as malnutrition and aspiration pneumonia. The use of screening instruments is essential for early detection and the reduction of hospital costs. The Oropharyngeal Dysphagia Screening for the Elderly (RaDI) stands out as a validated tool for geriatric populations, though it possesses potential for application in hospitalized adults. Objective: To describe the profile of hospitalized adults screened with the RaDI protocol and their clinical SLP outcomes during hospitalization. Methodology: This is a descriptive, quantitative, and retrospective study involving the analysis of secondary data from adults aged 18 to 59 years, admitted to a University Hospital between May 2023 and May 2024. The variables analyzed included sociodemographic data, RaDI scores, Functional Oral Intake Scale (FOIS) levels, and the requirement for SLP follow-up. Results: A total of 888 patients were screened, 84.6% of whom presented no risk for oropharyngeal dysphagia. Among patients with a RaDI score below 4, a subset required SLP intervention due to clinical progression during their hospital stay. Conclusions: It is estimated that the Oropharyngeal Dysphagia Screening for the Elderly (RaDI) can also be utilized for hospitalized adults, contributing to the enhancement of speech-language pathology clinical practice.